Recent Advances in Saturated N-Heterocycle C–H Bond Functionalization for Alkylated N-Heterocycle Synthesis - Zheng, Cameron H. M.; Schafer, Laurel L. (Synthesis, 2024)
The prominence of saturated N-heterocycle motifs in pharmaceuticals is undeniable. Challenges associated with the alkylation of saturated N-heterocycle scaffolds to efficiently access new drug analogues are hampered by synthetically laborious routes. Stereocontrolled alkyl-substitutions onto saturated N-heterocycles are particularly difficult to access in high yields by traditional synthetic methods. Alternatively, C–H bond functionalization provides a new and powerful synthetic avenue by directly and selectively functionalizing/alkylating/ arylating the abundantly available C–H bonds of saturated N-heterocycles. This review highlights complementary methods for directly activating and functionalizing C–H bonds of saturated N-heterocycles chemo-, regio-, and or stereoselectively to access alkylated products. This synthetic challenge has required catalyst development to access useful N-heterocyclic building blocks or for late-stage functionalization. Early transition metal, late transition metal, photoredox, and electrochemical methods are discussed. The selective functionalization of α, β, and γ C–H bonds to form new C–C, C–N, C–O, and C–B bonds is presented.1 Introduction2 Early Transition Metal Catalyzed α-Alkylation3 Late Transition Metal Catalyzed α-Functionalization4 Photoredox-Catalyzed α-Functionalization5 Electrochemical α-Functionalization6 C–H Functionalization of β and γ C–H Bonds7 Conclusions/Outlook
Keywords: amines; catalysis; electrocatalysis; photoredox catalysis; transition-metal catalysis; N-heterocycles; late-stage functionalization